Guignardia/Phyllosticta species on banana - Nilam F. Wulandari (2018)
Guignardia musae is the reported causal agent of freckle disease of banana. The epithet has, however, been introduced on three separate occasions and only one name is valid. We therefore investigated this problem. We examined the types of G. musae Racib., G. musae F. Stevens and G. musae Syd. & P. Syd. and also made fresh collections from banana in northern Thailand. Guignardia musae Racib. is the earliest name and takes precedence over the other two names which are hononyms. G. musae F. Stevens is a different species and therefore a new name G. stevensii Wulandari & K.D. Hyde is introduced to accommodate it. The name G. sydowiana Trotter has previously been introduced to accommodate G. musae Syd. & P Syd.; type material is, however, depauperate. Guignardia musicola Wulandari, L. Cai & K.D. Hyde sp. nov. is introduced as a new species from Thailand. The three species from banana are compared and their differences described. © 2010 Adac. Tous droits réservés.